The European Registered Toxicologist (ERT): Current status and prospects for advancement. (30th September 2016) - Wilks, Martin F.; Blaauboer, Bas J.; Schulte-Hermann, Rolf; Wallace, Heather M.; Galli, Corrado L.; Haag-Grönlund, Marie; Matović, Vesna; Teixeira, Joao Paulo; Zilliacus, Johanna; Basaran, Nursen; Bonefeld-Jørgensen, Eva Cecilie; Bourrinet, Philippe; et al.
Abstract: Following its inception in 1994, the certification of European Registered Toxicologists (ERT) by EUROTOX has been recognized as ensuring professional competence as well as scientific integrity and credibility. Criteria and procedures for registration are contained in the ERT "Guidelines for Registration 2012". The register of ERT currently has over 1900 members. In order to continue the harmonisation of requirements and processes between national registering bodies as a prerequisite for official recognition of the ERT title as a standard, and to take account of recent developments in toxicology, an update of the ERT Guidelines has been prepared in a series of workshops by the EUROTOX subcommittees for education and registration, in consultation with representatives of national toxicology societies and registers. The update includes details of topics and learning outcomes for theoretical training, and how these can be assessed. The importance of continuing professional development as the cornerstone of re-registration is emphasised. To help with the process of harmonisation, it is necessary to collate and share best practices of registration conditions and procedures across Europe. Importantly, this information can also be used to audit compliance with the EUROTOX standards. As recognition of professionals in toxicology, including specialist qualifications, is becoming more important than ever, we believe that this can best be achieved based on the steps for harmonisation outlined here together with the proposed new Guidelines.